2018
DOI: 10.1021/acs.joc.8b01372
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed (Z)-Selective Allylation of Nitroalkanes: Access to Highly Functionalized Homoallylic Scaffolds

Abstract: Nitroalkanes undergo decarboxylative allylation in the presence of vinyl-substituted cyclic carbonates, providing a wide variety of functionalized homoallylated compounds with exquisite stereocontrol. This Pd-mediated procedure features operational simplicity, versatile substrate combinations, and also allows for the sequential introduction of different allyl groups in the nitroalkane scaffolds with high levels of stereocontrol through the intermediacy of a ( Z)-configured palladacyclic intermediate. As far as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…This concept was first proved by Guo and co-workers using aryl amine nucleophiles toward the formation of highly functionalized (Z)-configured allylic alcohols/amines; the DFT (Density Functional Theory) studies suggested that the formation of a six-membered palladacyclic intermediate is the key for excellent stereocontrol [43]. Apart from amines, various other nucleophiles were demonstrated to be efficient for the syntheses of a huge number of allylic alcohols with excellent stereoselectivity (Scheme 10) [44][45][46][47]. By judicious choice of the palladium catalyst and ligand, the nucleophilic attack could be switched toward the sterically hindered carbon of the palladium allyl intermediate that derived from vinyl carbonate; this concept was first demonstrated by Guo and co-workers in the preparation of chiral α,α-disubstituted allylic aryl amines [48], and later it was further developed by the Khan group in the synthesis of chiral sulfones [49].…”
Section: Transition Metal-catalyzed Decarboxylation Of Cyclic Carbonatesmentioning
confidence: 99%
“…This concept was first proved by Guo and co-workers using aryl amine nucleophiles toward the formation of highly functionalized (Z)-configured allylic alcohols/amines; the DFT (Density Functional Theory) studies suggested that the formation of a six-membered palladacyclic intermediate is the key for excellent stereocontrol [43]. Apart from amines, various other nucleophiles were demonstrated to be efficient for the syntheses of a huge number of allylic alcohols with excellent stereoselectivity (Scheme 10) [44][45][46][47]. By judicious choice of the palladium catalyst and ligand, the nucleophilic attack could be switched toward the sterically hindered carbon of the palladium allyl intermediate that derived from vinyl carbonate; this concept was first demonstrated by Guo and co-workers in the preparation of chiral α,α-disubstituted allylic aryl amines [48], and later it was further developed by the Khan group in the synthesis of chiral sulfones [49].…”
Section: Transition Metal-catalyzed Decarboxylation Of Cyclic Carbonatesmentioning
confidence: 99%
“…Our group has focused on the functionalization of vinyl cyclic carbonates in palladium‐catalyzed allylic substitution reactions with different types of nucleophiles . Previously, we reported on a palladium‐catalyzed allylic alkylation combining modular VCCs and nitroalkanes as (pro)nucleophiles giving access to highly substituted, homoallylic nitroalkanes under excellent stereocontrol (Scheme ) . We envisioned that this type of readily accessible stereodefined homoallylic nitroalkanes would provide an excellent starting point for the preparation of indolizidine and quinolizidine alkaloids (Scheme ) in few overall synthetic manipulations by a double and appropriate cyclization strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Once the synthesis of VCCs 4 a – c was completed, the stereoselective, catalytic formation of homoallylic nitroalkanes was examined (Scheme B). Using already established conditions for this transformation, we successfully prepared compounds 5 a – d from VCCs 4 a – c and nitroalkanes C – D in 46–64 % yield while maintaining excellent stereocontrol in the olefin moiety. Importantly, the stereochemical configuration around the double bond achieved in this step is crucial to provide the requisite geometry for the subsequent cyclization steps affording the 1,2,3,6‐tetrahydropyridine ring present in the indolizidine and quinolizidine core.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of 9 reveals that the Pd center is η 3 ‐ligated by the allyl fragment and the hydromethyl group is orientated syn to the metal center. Such a π‐allyl Pd complex is rather distinct from the DFT‐computed six‐membered palladacycle recently determined in the functionalization of VECs with various nucleophiles ,,,. To examine whether this Pd‐complex 9 is catalytically competent, it was subjected to the optimized conditions reported in Table .…”
Section: Methodsmentioning
confidence: 99%